Philosophy, Analysis, and Games: The Futile Attempt of Defining Things [Filosofía, Análisis y Juegos: El Inútil Intento de Definir Las Cosas] - Briceno-Dominguez, J (Universidad Panamericana, 2020)
According to McGinn (2012), the aim of philosophy is to discover essences through conceptual analysis, and it qualifies as a game in Suits sense (1978; 2014). However, everything in Suits definition of game seems to exclude from its scope McGinn s definition of philosophy. Here I criticise McGinn s definition and offer a more comprehensive one. Incidentally, this definition will allow us to include philosophy within the class of activities that do satisfy Suits definition of game. © 2020 Universidad Panamericana. All rights reserved.